ANALISIS ENERGI DAN MUTU PRODUK PADA PROSES PEMASAKAN BUBUR KEDELAI DI INDUSTRI KECIL MENENGAH TAHU (Analysis of Energy and Product Quality in Soy Slurry Cooking in Small and Medium Enterprises of Tofu) - Afifah, Nok; Novrinaldi, Novrinaldi (Baristand Industri Banda Aceh, 2016)
Tofu is one of the small scale industries that use stoves with LPG or biomass as fuel. Thetypes of fuel, shapes and materials of stove are some factors that affect to the performance of the stove.The cooking process influence yield and the quality of the tofu. This study aimed to compare the energyrequirements and product quality of soy slurry cooking process in three small and medium enterprises oftofu which used different fuels (LPG, firewood and rice husk). This research was conducted with theobservations and direct measurements in the field by following the steps in the tofu production accordingto their usual procedures. Measurement parameters included the mass (weight) of material, the materialtemperature and cooking time. Furthermore, soybeans and soy slurry resulted from cooking process wereanalyzed in term moisture, ash, protein and fat. Soy slurry which cooked by LPG produced minimumspecific fuel consumption of 10.83 g per kg of soy slurry and minimum cooking time of 0.17 minute per kgof soy slurry. However, energy cost of LPG fuel was the highest, nearly 2 times the energy cost offirewood and rice husk. Economically, rice husk was the most efficient fuel. The addition of water duringthe cooking process produced soy slurry with water content in the range 91% -96%. Ash and fat contentwere not too reduced during cooking process, but the protein content decreased respectively by 13%, 26%and 32% in the use of LPG fuel, firewood, and rice husk. The optimum quality of soy slurry was obtainedby cooking using LPG.